Carbon Emission Disclosure, Environmental Performance, and Firm Value: The Role of Financial Performance - Gusti Ayu Ketut Rencana Sari Dewi (Jurnal Ilmiah Akuntansi, 2025)
This study investigates the direct and indirect effects of carbon emission disclosure and environmental performance on firm value, with financial performance acting as a mediating variable. The research is motivated by the growing demand for environmental accountability in corporate reporting and its potential impact on both financial outcomes and firm valuation. The study employs a quantitative approach using panel data derived from secondary sources, specifically annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2023. The population consists of firms in the raw materials and industrial sectors, with a final sample of 15 companies selected through purposive sampling. Path analysis with a random effects model is used to analyze the relationships among variables. The findings reveal that carbon emission disclosure and environmental performance do not have a significant effect on financial performance. However, carbon emission disclosure has a positive and significant effect on firm value, while environmental performance does not directly influence firm value. Financial performance is found to significantly affect firm value but does not mediate the relationship between carbon emission disclosure and firm value. Although financial performance does mediate the relationship between environmental performance and firm value, the effect is statistically insignificant. These results suggest that while environmental transparency may enhance firm valuation directly, its impact through financial performance remains limited. The study highlights the importance of carbon disclosure practices in signaling firm value and calls for further research on the mechanisms through which sustainability efforts influence financial outcomes.